Upaya Peningkatan Hasil Belajar Siswa Kelas V Pada Mata Pelajaran Bahasa Indonesia Melalui Metode Pembelajaran Role Playing di SDN Pandan - Mamluatur Rohmah; Agung Setyawan (Universitas Maritim AMNI Semarang, 2023)
The purpose of this study was to find out the learning outcomes of students at the elementary level through the Role Playing method. The learning outcomes of each student are different so there is a need for this research to examine this. Based on the results of student evaluations in learning material for fiction stories, fifth grade students at SDN Pandan showed very low learning evaluation results. This can be seen from several students, who obtained a 60% level of learning outcomes. This happens because of the lack of students in understanding the Role Playing material. This study uses a type of classroom action research using data collection techniques in the form of observation and tests. The research instrument used observation sheets in the form of teacher activity observation sheets and student observation sheets. The data analysis technique used is descriptive qualitative.